Artificial intelligence for healthcare and rescuing technology: technical developments and thoughts about employment impacts - Montemanni, Roberto (2019)
Introduction: To evaluate the overall impact of Artificial Intelligence (AI) and Robotics on employment and work organization is complicated by the fact that these technologies are expected to revolutionize many application fields, which are very different from each other. In this paper, we consider two specific applications emerging from recent research projects: one applies AI and Robotics technologies to the healthcare sector, and one to Search and Rescue in wilderness areas. We generalize from these case studies to speculate on how this kind of innovative applications, that are likely to become increasingly common and widespread, might impact employment and work organization in general. Objectives: To understand how innovative applications might impact employment and work organization in general and specifically on healthcare and social services. Methods: Two recent research developments based on the use of Artificial Intelligence (AI) in the fields of healthcare and rescuing, respectively, are discussed. Therefore, our research work and main results have been achieved within a Swiss National Science Foundation project and a simplified view of the innovative classification component of the architecture is presented. Results: AI and Robotics technologies have specific application on healthcare and social services and demand new professional skills to manage those new methods. Conclusions: We conclude that, depending on the application field, a reduction in the workforce required to carry out tasks that will be taken over by automation might be counterbalanced by either a drastic increase in demand (healthcare services), or a shift in the required competences/skills (search and rescue); in both cases, we can expect a positive societal impact, also motivated by an increased standard of service.